Food order affects blood glucose and insulin levels in women with gestational diabetes - Murugesan, Ria; Kumar, Janardanan; Thiruselvam, Shubhashree; Leela, Kakithakara Vajravelu; Geetha, K.; Satheesan, Abhishek; Chaithanya, Venkata; Angelin, Matcha (Frontiers in Nutrition, 2024)
BackgroundGestational diabetes mellitus (GDM) poses significant risks to both maternal and fetal health, including a heightened risk of developing type 2 diabetes (T2DM) in the future. Effective management often involves dietary changes, such as food-order, where vegetables are consumed first, followed by proteins, and then carbohydrates last. This study investigates whether food sequence improves glycemic control in women with GDM by slowing carbohydrate absorption, reducing glucose spikes, and enhancing insulin sensitivity.MethodsTwenty-five women with GDM participated in a four-week trial with three phases: baseline measurement (week 0), phase 1 (regular diet), and phase 2 (food-order) intervention. Primary outcomes were blood glucose and serum insulin levels, measured at fasting, 1-h, and 2-h postprandial intervals during each phase. In phase 1 (weeks 0–2), participants followed their usual diet. In phase 2 (weeks 2–4), the same participants followed a food-order regimen: vegetables first, then proteins, and carbohydrates last. Customized meal plans for vegetarians and non-vegetarians were provided. Participants were monitored via a mobile application (Jotform) for adherence. Follow-up blood glucose and insulin were measured before, and 60 and 120 min after, consuming a standardized meal (339 kcal, 16.4 g protein, 56.1 g carbohydrates, 3.4 g fat) in the clinic.ResultsThe food-order intervention resulted in a significant reduction in postprandial blood glucose by 5.87% (p = 0.001) at 60 min and 6.06% (p = 0.001) at 120 min. Also, Serum insulin levels decreased by 8.13% (p = 0.001) at 60 min and 11.10% (p = 0.001) at 120 min, compared to the regular diet. These results suggest improved metabolic control and insulin sensitivity.ConclusionPrioritizing vegetables before protein and carbohydrates improves glycemic control and insulin sensitivity in women with GDM. This simple strategy helps regulate blood glucose and may reduce the long-term risk of T2DM. It offers a practical approach to managing GDM, but further research with larger cohorts and longer interventions is needed to assess its long-term effects.Clinical trial registrationhttps://ctri.nic.in/Clinicaltrials/regtrial.php?modid=1&compid=19&EncHid=81473.12293, identifier CTRI/2024/01/061220.